PERLAWANAN PIHAK KETIGA (DERDEN VERZET) TERHADAP SITA EKSEKUSI TANAH ATAS PENETAPAN KETUA PENGADILAN NEGERI (ANALISIS PUTUSAN PENGADILAN NEGERI NO. 213/Pdt.Bth/2017/PN PLG) - Fiskarina Eka Rianti (Fakultas Hukum Universitas Sriwijaya, 2021)
Abstract:Basically, court proceedings can be carried out directly by parties who feel disadvantaged. A person or civil legal entity that feels that his interests have been impaired by a decision of the Chair of the District Court may file a written claim with the competent court. The injured party is not involved in a case, which is referred to as a third party. Which in this study the third party filed a derden verzet resistance to the district court in order to defend their rights in the case of seizure of the execution of the land that was the object of the dispute in the case. With which is the main problem in this study regarding the application of the principle or principle of prudence of judges in giving a fairest consideration to the parties, especially third parties, then the judge's consideration of Pekara No.213 / Pdt.Bth / 2017 / PN. PLG which is the subject of analysis in this study, also relates to the derden verzet resistance proposed by third parties in order to obtain justice, as well as the concept of the regulation of confiscation of execution in the future so as not to harm third parties. This study uses a research method that is normative legal research, which is based on the results of research applications submitted by third parties can not be accepted by the judge on the basis that the third party should submit an ordinary resistance is not derden verzet on the seizure imposed by the judge. Of course it does not provide justice for third parties, because judges are less careful and less careful in considering the main points which are argued on the basis of resistance proposed by third parties in the Palembang District Court.Keywords: Resistance, Derden Verzet, Third Party, District Court, Confiscation of Execution.